ELEMENTARY SCHOOL TEACHERS’ ACCEPTANCE OF WEBSITE-BASED MULTIMODAL MEDIA WITHIN A DEEP LEARNING APPROACH: A SUS ANALYSIS - Adestipa Adestipa; Yunus Abidin; Dede Trie Kurniawan (Program Studi PGSD Universitas Flores, 2025)
Although various educational technology innovations have been developed, the level of acceptance and readiness among elementary school teachers to integrate AI-based learning media, particularly those employing deep learning approaches, remains a challenge due to limited pedagogical understanding and varying levels of technological literacy among educators. This study aims to analyze the level of acceptance among elementary school teachers toward website-based multimodal learning media developed using a deep learning approach. The media is designed to enrich students' learning experiences through the integration of text, images, audio, and video, adaptively organized by a web-based system. The research method employed was a quantitative survey using the System Usability Scale (SUS) questionnaire, administered to 80 elementary school teachers as respondents located in Bandung Regency, providing quantitative assessments of the ease of use and user acceptance of the developed media. The analysis results indicate that the media obtained an average SUS score of 78, falling within the “good” category and approaching the “widely accepted” level. Teachers assessed the media as effective, engaging, and relevant to twenty-first-century learning needs. These findings indicate that the deep learning approach in developing website-based multimodal learning media holds significant potential for widespread implementation in elementary education settings.